Sewage sludge from Taxco de Alarcón wastewater treatment plant as substrate to cultivate Panicum maximum - Erik Yoel Carreto-Morales; Jazmin Alaide López-Díaz; Mariana Martínez-Castrejón; Oscar Talavera-Mendoza; Roberto Carlos Almazán-Núñez; Giovanni Hernández-Flores (Revista Mexicana de Ciencias Geológicas)
The management and disposal of the sewage sludge (SS) generated by a wastewater treatment plant (WWTP) as part of the municipal wastewater (MWW) treatment process is one of the main socio-environmental issues faced by this type of system. Taxco de Alarcón, Guerrero, in southern Mexico has had a WWTP operating since 2016, and the SS disposal is a task that must be addressed by the WWTP. Thus, the aim of this work was to evaluate the growth capacity of Panicum maximum, also known as mombaza grass (MG), by using SS generated within the "Taxco de Alarcón wastewater treatment plant" as substrate. To do so, 4 g of MG seeds were scattered over 5 kg (dry basis) of SS. As a control, a commercial compost soil was used, hereafter called pattern soil (PS). The experiment was carried out in triplicates for three months and drinking water (water used for human consumption) was used for crop irrigation. Each month a MG harvest was carried out. The response variables analyzed for MG were germination time (one month after plant emergence), height (HMG), growth rate GrMG, and yield (YMG), whereas in the SS and PS the content of organic matter was analyzed. Furthermore, the chemical composition was analyzed using scanning electron microscopy and X-ray energy dispersion spectroscopy (SEM-EDS) on the MG, SS, and PS. The results showed that MG germinated faster on PS (5 days) than germination on SS (7 days). However, the MG grown on SS reached a considerably higher height (45 cm) compared to the height reached on PS (17 cm). Furthermore, the maximum GrMG over SS was also higher than the maximum GrMG observed on the PS, 3.64 and 1.40 cm∙day-1, respectively. In terms of YMG, it was observed that on SS it reached an average monthly YMG of 416 g∙m-2, whereas in PS it reached a YMG of 72 g∙m-2. The chemical analysis detected P, K, Ca, Mg, and S, considered macronutrients in both substrates. Besides, some micronutrients identified in SS were Cu, Fe, Mn, and Zn, whereas in PS it was also possible to detect micronutrients except Mn and Zn. All the macronutrients detected in the substrates were observed in the harvested MG. However, in the MG harvested in PS, Mn and Zn were not detected. Hence, a feasible disposal strategy for the SS generated by the Taxco de Alarcón WWTP is as a substrate for grass forage MG by its high organic matter content, the significant presence of macro and micronutrients, and the performance shown by MG cultivated in SS. Furthermore, the SS characteristics provide added value and can be considered as organic amendments of agricultural soils.